A conductive silver paste for N-type TOPCon back side grid and its preparation method

By using a specific composition of conductive silver paste, including monodispersed spherical silver powder, lead-bismuth tellurium main glass, lead-boron auxiliary glass and organic adhesive, the problem of difficult to optimize ohmic resistance and carrier mobility in N-TOPCon solar cells is solved, and a higher photoelectric conversion efficiency is achieved.

CN116598043BActive Publication Date: 2025-03-04NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310711321.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2025-03-04
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

It is difficult for existing N-TOPCon solar cells to achieve smaller ohmic resistance and higher carrier mobility at the same time, affecting the photoelectric conversion efficiency.

Method used

The N-type TOPCon back sub-gate conductive silver paste prepared with monodispersed spherical silver powder, lead-bismuth tellurium main glass, lead-bismuth tellurium main glass, lead-bismuth tellurium auxiliary glass, silicon powder and organic binder is improved by adjusting the mass ratio of lead-bismuth tellurium main glass and lead-bismuth tellurium auxiliary glass, and optimizing the composition and proportion of organic binder, the contact resistance and carrier mobility of the silver paste are improved.

Benefits of technology

Low contact resistance and saturation current density values ​​are achieved, and the open circuit voltage, short circuit current and fill factor are improved, thereby improving the photoelectric conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004287765840000101
    Figure BDA0004287765840000101
  • Figure BDA0004287765840000111
    Figure BDA0004287765840000111
  • Figure BDA0004287765840000112
    Figure BDA0004287765840000112
Patent Text Reader

Abstract

The present invention belongs to the field of electricity, and in particular to the field of H01B1 / 16, and more specifically to a conductive silver paste for the back side grid of N-type TOPCon and a preparation method thereof. The raw materials for its preparation include at least 85-95% of monodisperse spherical silver powder, 2%-3% of lead bismuth telluride main glass, 0.1-0.3% of lead boron auxiliary glass, 0.05-0.2% of silicon powder, and 2%-10% of organic adhesive. The N-type TOPCon solar cell prepared by the present invention not only has a lower contact resistance and saturation current density value, but also can improve the open circuit voltage, short circuit current, filling factor, etc., thereby improving the photoelectric conversion efficiency of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electricity, in particular to the field of H01B1 / 16, and more specifically to a conductive silver paste for an N-type TOPCon back side sub-gate and a preparation method thereof. Background Art

[0002] N-type TOPCon (Tunnel Oxide Passivated Contact) cells are basically a basic architecture based on PERC cells. The theoretical efficiency limit of TOPCon cells is as high as 28.7%, which is the technology closest to the theoretical efficiency limit of crystalline silicon solar cells (29.43%), much higher than the emitter and back passivation cell technology PERC (24.5%). N-type cells will become the future direction of battery technology development. Conductive paste is an important raw material for crystalline silicon solar cells, and its performance has a decisive influence on the efficiency and production cost of crystalline silicon solar cells. Conductive paste is generally composed of metal conductive materials, organic carriers, adhesives, solvents, etc., and can be roughly divided into four types according to the purpose and printing location: front silver aluminum paste, front main grid silver paste, back main grid silver paste and back sub-grid silver paste. The efficiency of conductive silver paste in absorbing current determines the photoelectric conversion efficiency of crystalline silicon solar cells. Therefore, the paste needs to have good contact with the silicon substrate. The smaller the contact resistance, the better the conductivity and the higher the efficiency. At the same time, it is also necessary to reduce the carrier recombination rate as much as possible and increase the carrier mobility, thereby promoting the improvement of the photoelectric conversion efficiency of the battery.

[0003] The prior art is that CN115732118A discloses a low-temperature sintered silver-aluminum paste for N-TOPCon solar cells, and its preparation method and application, and its preparation raw materials include silver powder, aluminum-gallium alloy powder, glass powder, fluoroborate, additives and solvents. The invention uses aluminum-gallium alloy powder to replace traditional aluminum powder, and introduces fluoroborate at the same time, which can avoid the need for a high sintering temperature for battery metallization; the prior art is that CN115440409A discloses a silver-aluminum paste for N-TOPCon solar cells, and its preparation raw materials include silver powder, aluminum powder, additives and solvents. The silver-aluminum paste can reduce contact resistance and slow down aluminum-silicon eutectic, and improve the electrical performance of solar cells. However, it is difficult for the above-mentioned N-TOPCon to achieve both a low ohmic resistance and a high carrier mobility at the same time. Therefore, it has become a hot topic to develop an excellent N-type TOPCon back-side secondary grid conductive silver paste that can have a good ohmic contact with the silicon wafer and achieve a low ohmic resistance and carrier recombination rate. Summary of the invention

[0004] In order to solve the above problems, the first aspect of the present invention provides a conductive silver paste for the back side sub-gate of N-type TOPCon, and the raw materials for its preparation include at least 85-95% of monodisperse spherical silver powder; 2%-3% of lead bismuth telluride main glass; 0.1-0.3% of lead boron auxiliary glass; 0.05-0.2% of silicon powder; and 2%-10% of organic adhesive.

[0005] Preferably, the monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0006] Preferably, the D50 particle size of the lead bismuth telluride main glass is 2-4 μm.

[0007] Further preferably, the lead bismuth telluride main glass component includes, by mass percentage, 20% to 25% of Pb-containing compounds, 10% to 15% of Bi-containing compounds, 18% to 23% of Te-containing compounds, and the remainder includes one or more of Cu-containing compounds, Sc-containing compounds, Ti-containing compounds, and Zn-containing compounds.

[0008] The above-mentioned compound may include oxides, silicides, silicates, carbides, chlorides, etc. For example, the Pb-containing compound may include oxides, silicides, silicates, carbides, chlorides, etc. of Pb.

[0009] Preferably, the Pb-containing compound includes lead oxide, the Bi-containing compound includes bismuth trioxide, the Te-containing compound includes tellurium dioxide, the Cu-containing compound includes copper oxide, the Sc-containing compound includes scandium oxide, the Ti-containing compound includes titanium dioxide, and the Zn-containing compound includes zinc oxide.

[0010] Preferably, the D50 particle size of the lead-boron auxiliary glass is 2 to 4 μm.

[0011] Further preferably, the lead-boron auxiliary glass component includes, by mass percentage, 35% to 40% of Pb-containing compounds, 25% to 30% of B-containing compounds, and the remainder includes one or more of Cu-containing compounds, Sc-containing compounds, Ti-containing compounds, Te-containing compounds, Zn-containing compounds, and Ga-containing compounds.

[0012] The above-mentioned compounds may include oxides, silicides, silicates, carbides, chlorides, etc. For example, the Pb-containing compound may include oxides, silicides, silicates, carbides, chlorides, etc. of Pb. Preferably, the Pb-containing compound includes lead oxide, the B-containing compound includes boron trioxide, and the Ga-containing compound includes gallium trioxide.

[0013] Further preferably, the mass ratio of the lead bismuth telluride main glass to the lead boron auxiliary glass is (2.5-3.0): (0.1-0.3).

[0014] The Pb-containing compound in the present invention has excellent properties such as lowering the melting temperature of glass, improving the wettability of glass and increasing the resistivity of glass. The lead-containing glass powder has great advantages in terms of gloss, thermal expansion coefficient, mechanical strength and electrical properties. There is a certain relationship between the boron content and the contact resistance of the battery. As the boron content increases, the value of the contact resistance first decreases and then increases. The inventors found that when the mass ratio of the lead-bismuth-tellurium main glass and the lead-boron auxiliary glass is (2.5-3.0): (0.1-0.3), the contact resistance of the conductive paste of the present invention is low. When the content of the lead-boron auxiliary glass is too little, the contact resistance of the system is large, which affects the photoelectric conversion efficiency of the battery. When the content of the lead-boron auxiliary glass is too large, due to the strong corrosiveness of the lead-boron auxiliary glass, the Poly (polycrystalline silicon) layer on the back of the N-type solar cell will be corroded too deeply, resulting in an increase in the lateral resistance, thereby affecting the photoelectric conversion efficiency of the battery.

[0015] Preferably, the silicon powder is mainly composed of elemental silicon, and the remainder includes one or more of Sr-containing compounds, Zr-containing compounds, and Mo-containing compounds.

[0016] The above-mentioned compound may include oxides, silicides, silicates, carbides, chlorides, etc. For example, the Sr-containing compound may include oxides, silicides, silicates, carbides, chlorides, etc. of Sr.

[0017] Further preferably, the Sr-containing compound includes strontium oxide, the Zr-containing compound includes zirconium dioxide, and the Mo-containing compound includes molybdenum oxide.

[0018] Elemental silicon can reduce the interface state density between Poly-Si and silicon nitride. The majority carrier concentration is much higher than the minority carrier concentration, which reduces the probability of electron-hole recombination while increasing the resistivity to form selective contact for majority carriers. In the selective contact area, majority carrier transmission leads to resistance loss, while a small amount of minority carriers migrate to the metal contact area, leading to recombination loss, thereby reducing the saturation current density J0 value and reducing carrier recombination.

[0019] Preferably, the organic adhesive comprises: resin, solvent and dispersant.

[0020] Preferably, the mass ratio of the resin, solvent and dispersant is (3-6): (0.5-1.5): (1.5-2.5).

[0021] The organic adhesive in the present invention comprises: resin, solvent and dispersant. The resin can not only promote the bonding strength between the conductive silver paste and the silicon layer, but also promote the dissolution of monodisperse spherical silver powder, lead bismuth tellurium main glass and lead boron auxiliary glass, and especially reduce the sintering temperature of the battery. Since the dispersibility of each raw material in the system of the present invention is poor, it is easy to cause the powders to agglomerate over time, thereby affecting the performance of the battery. The specific dispersant can not only better disperse the substances in the system and quickly wet the battery surface, but also increase the energy barrier between solid particles to a high enough level, which can effectively reduce the contact resistance. When the mass ratio of the resin, solvent and dispersant in the organic adhesive is (3-6): (0.5-1.5): (1.5-2.5), the three work together, not only can the slurry and the silicon wafer be more firmly attached, but also can reduce the contact resistance of the battery, thereby improving the photoelectric conversion efficiency of the solar photovoltaic cell.

[0022] Further preferably, the resin includes at least one or more of ethyl cellulose, cellulose acetate, PVB resin, and epoxy resin.

[0023] Further preferably, the solvent includes at least one of ethylene glycol butyl ether, diethylene glycol butyl ether, diethylene glycol acetate, and tributyl citrate.

[0024] Further preferably, the dispersant includes at least one of polyether, polyacrylate and phosphate ester.

[0025] A second aspect of the present invention provides a method for preparing a conductive silver paste for an N-type TOPCon back side grid, comprising at least the following steps:

[0026] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead bismuth telluride main glass, lead boron auxiliary glass, silicon powder, and organic adhesive on an electronic balance and blend them;

[0027] S2, centrifugation: putting the blended materials into a centrifuge for preliminary mixing of the materials;

[0028] S3, three-roll mill: Use a three-roll mill to fully mix the slurry obtained by centrifugation.

[0029] Beneficial Effects

[0030] (i) In the present invention, an N-type TOPCon solar cell is prepared by using specific raw materials of monodisperse spherical silver powder, lead bismuth telluride main glass, lead boron auxiliary glass, silicon powder, and organic adhesive, which not only has a lower contact resistance and saturation current density value, but also can improve the open circuit voltage, short circuit current, fill factor, etc., thereby improving the photoelectric conversion efficiency of the solar cell.

[0031] (ii) In the present invention, by limiting the mass ratio of lead bismuth telluride main glass to lead boron auxiliary glass to (2.5-3.0): (0.1-0.3), the contact resistance of the system can be reduced and the silicon wafer will not be excessively corroded.

[0032] (III) In the present invention, silicon powder is used to reduce the interface state density between Poly-Si and silicon nitride, thereby reducing the saturation current density J0 value of the battery.

[0033] (IV) In the present invention, by limiting the mass ratio of the resin, the solvent, and the dispersant in the organic adhesive to (3-6): (0.5-1.5): (1.5-2.5), not only can the adhesion between the slurry and the silicon wafer be made stronger, but also the contact resistance can be reduced, thereby improving the photoelectric conversion efficiency of the solar photovoltaic cell.

[0034] (V) The preparation method of the N-type TOPCon solar cell of the present invention is simple. Through centrifugation and three-roll grinding, the mixing of the various preparation raw materials can be made more uniform, and the attachment of the preparation raw materials to the silicon wafer can be more firmly, so that the N-type TOPCon solar cell has better electrical performance. DETAILED DESCRIPTION

[0035] Example 1

[0036] In a first aspect, the present embodiment provides a conductive silver paste for the back side sub-gate of an N-type TOPCon, wherein the raw materials for preparing the paste are, by mass percentage, 87.8% of monodisperse spherical silver powder, 2.8% of lead bismuth telluride main glass, 0.3% of lead boron auxiliary glass, 0.1% of silicon powder, and 9% of an organic adhesive.

[0037] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0038] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 15% titanium dioxide, and 20% zinc oxide.

[0039] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0040] The D50 particle size of the silicon powder is 2-4 μm, and the specific components are 95% elemental silicon, 2% SrO, 2% ZrO2, and 1% MoO3.

[0041] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0042] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0043] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, silicon powder, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0044] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0045] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0046] Example 2

[0047] In a first aspect, the present embodiment provides a conductive silver paste for the back side sub-gate of an N-type TOPCon, wherein the raw materials for preparing the paste are as follows in terms of mass percentage: 88% monodisperse spherical silver powder, 2.8% lead bismuth telluride main glass, 0.1% lead boron auxiliary glass, 0.1% silicon powder, and 9% organic adhesive.

[0048] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0049] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 15% titanium dioxide, and 20% zinc oxide.

[0050] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0051] The D50 particle size of the silicon powder is 2-4 μm, and the specific components are 95% elemental silicon, 2% SrO, 2% ZrO2, and 1% MoO3.

[0052] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0053] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0054] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, silicon powder, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0055] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0056] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0057] Example 3

[0058] In a first aspect, the present embodiment provides a conductive silver paste for the back side sub-gate of an N-type TOPCon, wherein the raw materials for preparing the paste are as follows in terms of mass percentage: 88.05% monodisperse spherical silver powder, 2.8% lead bismuth telluride main glass, 0.1% lead boron auxiliary glass, 0.05% silicon powder, and 9% organic adhesive.

[0059] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3.

[0060] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 15% titanium dioxide, and 20% zinc oxide.

[0061] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0062] The D50 particle size of the silicon powder is 2-4 μm, and the specific components are 95% elemental silicon, 2% SrO, 2% ZrO2, and 1% MoO3.

[0063] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0064] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0065] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, silicon powder, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0066] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0067] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0068] Comparative Example 1

[0069] The first aspect of the present comparative example provides a conductive silver paste for the back side sub-gate of N-type TOPCon, wherein the raw materials for its preparation are, by mass percentage, 87.6% of monodisperse spherical silver powder, 2.8% of lead bismuth telluride main glass, 0.5% of lead boron auxiliary glass, 0.1% of silicon powder, and 9% of organic adhesive.

[0070] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0071] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 17% titanium dioxide, and 18% zinc oxide.

[0072] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0073] The D50 particle size of the silicon powder is 2-4 μm, and the specific components are 95% elemental silicon, 2% SrO, 2% ZrO2, and 1% MoO3.

[0074] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0075] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0076] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, silicon powder, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0077] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0078] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0079] Comparative Example 2

[0080] The first aspect of the present comparative example provides a conductive silver paste for the back side grid of N-type TOPCon, wherein the raw materials for its preparation are as follows by mass percentage: 88% monodisperse spherical silver powder, 2.9% lead bismuth telluride main glass, 0.1% silicon powder, and 9% organic adhesive.

[0081] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0082] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 17% titanium dioxide, and 18% zinc oxide.

[0083] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0084] The D50 particle size of the silicon powder is 2-4 μm, and the specific components are 95% elemental silicon, 2% SrO, 2% ZrO2, and 1% MoO3.

[0085] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0086] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0087] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead bismuth tellurium main glass, silicon powder, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0088] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0089] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0090] Comparative Example 3

[0091] The first aspect of the present comparative example provides a conductive silver paste for the back side sub-gate of N-type TOPCon, wherein the raw materials for its preparation are as follows in terms of mass percentage: 87.9% monodisperse spherical silver powder, 2.8% lead bismuth telluride main glass, 0.3% lead boron auxiliary glass, and 9% organic adhesive.

[0092] The monodisperse spherical silver powder has a D50 particle size of 1 to 2 μm and a specific surface area of ​​0.4 to 0.8 m 2 / g, tap density 5~9g / cm 3 .

[0093] The D50 particle size of the lead-bismuth-telluride main glass is 2-4 μm, and the specific components are 23% lead oxide, 14% bismuth trioxide, 22% tellurium dioxide, 6% copper oxide, 17% titanium dioxide, and 18% zinc oxide.

[0094] The D50 particle size of the lead-boron auxiliary glass is 2-4 μm, and the specific components are 37% lead oxide, 30% boron trioxide, 13% tellurium dioxide, 5% copper oxide, 7% titanium dioxide, and 8% zinc oxide.

[0095] The organic adhesive is resin, solvent and dispersant; the mass ratio of resin, solvent and dispersant is 5:1:1.5; the resin is ethyl cellulose, cellulose acetate, PVB resin, epoxy resin and rosin resin, and the mass ratio is 2:3:8:6:7; the solvent is ethylene glycol butyl ether, diethylene glycol butyl ether and tributyl citrate, and the mass ratio is 1.5:1:1; the dispersant is polyether, polyacrylate and phosphate, and the mass ratio is 1.2:1:1.1.

[0096] A second aspect of the present embodiment provides a method for preparing a conductive silver paste for a back side sub-gate of an N-type TOPCon, which comprises the following steps:

[0097] S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, and organic adhesive according to mass percentage on an electronic balance and blend them;

[0098] S2. Centrifugation: The blended material is placed in a centrifuge and centrifuged twice to preliminarily mix the material; the centrifugal speed is 550 rpm, the centrifugal time is 5 min, and the material is manually stirred after one centrifugation.

[0099] S3, three-roller: Use a three-roller grinder to fully mix the slurry obtained by centrifugation, set the spacing 1 and spacing 2 of the three rollers to 50μm, 30μm; 30μm, 15μm; 15μm, 8μm; 15μm, 8μm, respectively, set the speed to 150rpm, repeat the rolling four times, and the final product fineness is less than 10μm, that is, the N-type TOPCon back side sub-gate conductive silver paste is obtained.

[0100] Performance Evaluation

[0101] 1: Resistance related performance test

[0102] Test object: N-type TOPCon back side grid conductive silver paste prepared in Example 1-3 and Comparative Example 1-2

[0103] Contact resistance test: Use a contact resistance tester to perform linear fitting through the TLM method, reverse the square resistance to obtain the ohmic contact resistance, and record the results in Table 1

[0104] The line width, line height and cross-sectional area are measured by a 3D profiler. After the sample is placed, the data can be automatically measured and the results are recorded in Table 1.

[0105] Table 1

[0106]

[0107]

[0108] It can be seen from the experimental data that when the addition amount of lead-boron glass is between 0.1% and 0.3%, it has a significant reducing effect on the contact resistance, and when the addition amount reaches 0.5%, the contact resistance increases. This is because lead-boron glass is highly corrosive and corrodes the Poly layer on the back of the N-type solar cell too deeply, resulting in an increase in lateral resistance.

[0109] 2: Saturation current density (J0), open circuit voltage test

[0110] Test objects: Example 2, Example 3, Comparative Example 3

[0111] Test items: open circuit voltage Voc, saturation current density

[0112] Test instrument: WCT-120 instrument measures minority carrier lifetime and obtains composite size through linear fitting Test conditions: STC, 25℃, 1000W / m 2 , and record the results in Table 2

[0113] Table 2

[0114]

[0115] The relevant data of minority carrier lifetime measured by WCT-120 are linearly fitted, and the a value can reflect the size of the saturation current density, among which the b value and r can reflect the situation of the fitting line. From the above experimental results, the addition of silicon powder greatly reduces the recombination of carriers.

[0116] 3. Client comparison test

[0117] Test objects: client base sample (denoted as BSL2) and N-type TOPCon back side sub-gate conductive silver paste prepared in Example 2.

[0118] Test method: Test on the client side. The contact resistance test uses a contact resistance tester, and linear fitting is performed through the TLM method to reversely infer the square resistance to obtain the ohmic contact resistance. The IV curve tester is used to test the open circuit voltage, short circuit current and cell efficiency, where the open circuit voltage, short circuit current and FF can all correspond to the contact resistance and carrier recombination size, and the results are recorded in Table 3.

[0119] The saturation current density (J0) was used to measure the minority carrier lifetime using a WCT-120 instrument, and the carrier recombination size was obtained by linear fitting.

[0120] Table 3

[0121]

[0122] Example 2 uses main glass + auxiliary glass + silicon powder. Compared with the client base sample, Eta is improved, contact resistance is reduced, and carrier recombination is reduced.

Claims

1. A conductive silver paste for the back side grid of N-type TOPCon, characterized by: The raw materials for its preparation include at least 85-95% of monodisperse spherical silver powder, 2%-3% of lead-bismuth-telluride main glass, 0.1-0.3% of lead-boron auxiliary glass, 0.05-0.2% of silicon powder, and 2%-10% of organic adhesive. The D50 particle size of the lead bismuth telluride main glass is 2-4µm; The lead-bismuth-tellurium main glass comprises, by mass percentage, 20% to 25% of a Pb-containing compound, 10% to 15% of a Bi-containing compound, 18% to 23% of a Te-containing compound, and the remainder comprises one or more of a Cu-containing compound, a Sc-containing compound, a Ti-containing compound, and a Zn-containing compound; The D50 particle size of the lead-boron auxiliary glass is 2~4µm; The lead-boron auxiliary glass component includes, by mass percentage, 35% to 40% of a Pb-containing compound, 25% to 30% of a B-containing compound, and the remainder includes one or more of a Cu-containing compound, a Sc-containing compound, a Ti-containing compound, a Te-containing compound, a Zn-containing compound, and a Ga-containing compound; The mass ratio of the lead-bismuth-tellurium main glass to the lead-boron auxiliary glass is (2.5-3.0): (0.1-0.3); The silicon powder is mainly composed of elemental silicon, and the remainder includes one or more of Sr-containing compounds, Zr-containing compounds, and Mo-containing compounds; The D50 particle size of the silicon powder is 2-4 μm.

2. The conductive silver paste for the back side grid of N-type TOPCon according to claim 1, characterized in that: The monodisperse spherical silver powder has a D50 particle size of 1-2 µm and a specific surface area of ​​0.4-0.8 m 2 / g, tap density 5~9g / cm 3 .

3. The conductive silver paste for the back side grid of N-type TOPCon according to claim 1, characterized in that: The organic adhesive comprises resin, solvent and dispersant.

4. The conductive silver paste for the back side grid of N-type TOPCon according to claim 3, characterized in that: The mass ratio of the resin, solvent and dispersant is (3-6): (0.5-1.5): (1.5-2.5).

5. The conductive silver paste for the back side grid of N-type TOPCon according to claim 4, characterized in that: The resin includes at least one of ethyl cellulose, cellulose acetate, PVB resin and epoxy resin.

6. The conductive silver paste for the back side grid of N-type TOPCon according to claim 4, characterized in that: The dispersant includes at least one of polyether, polyacrylate and phosphate.

7. A method for preparing an N-type TOPCon back side secondary grid conductive silver paste according to any one of claims 1 to 6, characterized in that: At least the following steps are included: S1. Ingredients: accurately weigh monodisperse spherical silver powder, lead-bismuth-tellurium main glass, lead-boron auxiliary glass, silicon powder, and organic adhesive on an electronic balance and blend them; S2, centrifugation: putting the blended materials into a centrifuge for centrifugation to preliminarily mix the materials; S3, three-roll mill: Use a three-roll mill to fully mix the slurry obtained by centrifugation.

Citation Information

Patent Citations

  • Silver-aluminum paste for N-TOPCon solar cell as well as preparation method and application of silver-aluminum paste

    CN115440409A

  • Low-temperature sintered silver-aluminum paste for N-TOPCon solar cell and preparation method and application of low-temperature sintered silver-aluminum paste

    CN115732118A

  • Silver paste of high-performance lead-free crystalline silicon solar battery back electrode and preparation method thereof

    CN106128553A

  • Main grid silver paste for silicon solar cell and preparation method thereof

    CN114843005A